Greener Routes to Biomass Waste Valorization: Lignin Transformation Through Electrocatalysis for Renewable Chemicals and Fuels Production. Issue 17 (1st July 2020) - Garedew, Mahlet; Lin, Fang; Song, Bing; DeWinter, Tamara M.; Jackson, James E.; Saffron, Christopher M.; Lam, Chun Ho; Anastas, Paul T.
Abstract: Lignin valorization is essential for biorefineries to produce fuels and chemicals for a sustainable future. Today's biorefineries pursue profitable value propositions for cellulose and hemicellulose; however, lignin is typically used mainly for its thermal energy value. To enhance the profit potential for biorefineries, lignin valorization would be a necessary practice. Lignin valorization is greatly advantaged when biomass carbon is retained in the fuel and chemical products and when energy quality is enhanced by electrochemical upgrading. Though lignin upgrading and valorization are very desirable in principle, many barriers involved in lignin pretreatment, extraction, and depolymerization must be overcome to unlock its full potential. This Review addresses the electrochemical transformation of various lignins with the aim of gaining a better understanding of many of the barriers that currently exist in such technologies. These studies give insight into electrochemical lignin depolymerization and upgrading to value‐added commodities with the end goal of achieving a global low‐carbon circular economy. Abstract : Electrons to Molecules : Rather than lignin's use as a source of low‐value heat and power, electrocatalysis provides the means for valorizing lignin and its aromatics to higher‐value fuels and chemicals. Electrochemical methods provide tunable selectivity via the control of electrical potential while eliminating the need for oxidizing/reducing reagents and allow for the direct integration of renewable energy to facilitate chemical transformations.